Measurement of Radium and Radon Exhalation Rate in Marble Samples used in Al-Bayda City Market-Libya - Ali, Jemila M.; Ibrahim, Suhayla A. (Al-Mukhtar Journal of Sciences, 2022)
The aim of the present study is to measure the activity concentrations of  226Ra, 222Rn, the mass exhalation rate of 222Rn, and the annual effective dose of radon in marble samples collected from Al-Bayda  city local market –Libya. Samples were measured by using a low-background NaI (Tl) detector. The average activity concentrations of 226Ra and 222Rn were 72.57 Bq.kg-1 and 597.85 Bq.m-3.The radon exhalation rate in marble samples vary from 0.05-0.30 Bq.kg-1.S-1 with an average of 0.13 Bq.kg-1.S-1. The annual effective dose of radon was calculated in samples under investigation. For most samples, the values were lower than the maximum permissible dose limits. It can be concluded that marble samples under investigation do not pose any radiological hazard to the dwellers of buildings used in their construction.